Courts, doctrine and inclusive society: Brief notes based on the synthesis of the results of research - Palici di Suni, Elisabetta (2019)
This article contains the results of the level of influence exercised by the doctrine on the judgments passed by the constitutional courts, distinguishing between the courts that quote the doctrine and others that do not, based on such influence. To this effect, it differentiates the courts according to their jurisdiction, but, also, of style, according to their specific legal system as well. Likewise, this subject is addressed from both a historical and cultural perspective.